Cultivation of Perilla frutescens (Lamiaceae) in prehistoric Korea. (December 2021) - Li, Brian; Kim, Minkoo
Highlights: We present evidence of perilla seed storage dated to ca. 1000 BC. Experiments were conducted to examine seed-size changes under carbonization. The seeds are identified to be Perilla frutescens var . frutescens. People on the Korean Peninsula utilized Perilla sp. from 3500 BC. Aromatic plants were cultivated on a small scale along with cereals and legumes. Abstract: The Mumun period (ca. 1500–1 BC) on the Korean Peninsula represents an incipient agricultural society with a reliance on cereals and legumes. Relatively little is known about the utilization of other types of plants that are considered to be delicacies and condiments. We present archaeobotanical evidence of the storage of perilla seeds dated to ca. 1000 BC. Charring experiments of modern perilla seeds were conducted to examine seed-size changes under different heating temperatures and durations. The experimental results confirmed that the recovered specimens belonged to the cultivated type of Perilla frutescens var . frutescens. The occasional discovery of perilla seeds from earlier settlements suggests that perilla utilization has a deeper history that dates back to ca. 3500 BC. These findings demonstrate that the small-scale production of fragrant vegetables and oilseeds was important alongside the cultivation of carbohydrate-rich crops in prehistoric Korea.